1991
DOI: 10.1111/j.1468-232x.1991.tb00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing and Firm Performance in Japan

Abstract: North American firms have begun to show greater interest in sharing private business information with unions and employees, a labor relations practice widely institutionalized in Japan. This study uses a survey of Japanese joint consultation committees and publicly available business data to examine the effects of information sharing on a firm's profitability, productivity, and labor cost. The results generally show a positive association of information sharing with profitability and productivity and a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 20 publications
5
46
0
4
Order By: Relevance
“…A study by Hamid (2013) found a significant positive relationship between knowledge sharing and firm performance. This is consistent with the result by Morishima (1991) and Marchington, Wilkinson, Ackers and Goodman (1994). It was also acknowledged that the current challenges facing firms is not to simply implement but to think and solve problems by sharing information (Hamid, 2013).…”
Section: The Relationship Between Knowledge Sharing and Intangible Pesupporting
confidence: 79%
“…A study by Hamid (2013) found a significant positive relationship between knowledge sharing and firm performance. This is consistent with the result by Morishima (1991) and Marchington, Wilkinson, Ackers and Goodman (1994). It was also acknowledged that the current challenges facing firms is not to simply implement but to think and solve problems by sharing information (Hamid, 2013).…”
Section: The Relationship Between Knowledge Sharing and Intangible Pesupporting
confidence: 79%
“…Factor of good communication was also suggested by De Silva (1996) that workers and employers had to make an effective communication without misunderstanding. Factor of data revealing is similar to the suggestion of Morishima (1991) on information sharing between workers and managers but the result showed that both sides need trust between them too. Factor of worker's participation was suggested by Inoue (1991) on union's participation in the process of decision making of the organization, De Silva (1998) also stressed on the factors of sound labor relations of worker participation and employee involvement.…”
Section: Labor Law and Government Policysupporting
confidence: 59%
“…De Silva (1996) suggested that workers and employers had to negotiate with the recognition of each other and bargain in good faith, make a compromise for solution with effective communication without misunderstanding. Morishima (1991) explained sound labor relations in Japan by the system of joint consultation and information sharing between workers and managers. Inoue (1991) added that sound labor relations need good communication of workers and employers, and the union should participate in the process of decision making of the organization.…”
Section: Concept Of Sound Labor Relationsmentioning
confidence: 99%
“…(Tremblay et al, 2005a : 73). Malgré tous les bienfaits que certaines études lui attribuent comme processus organisationnel influençant activement les relations entre les pratiques de gestion des ressources humaines et la performance (Morishima, 1991 ;Becker et Huselid, 1999), peu de recherches empiriques ont intégré cette pratique comme antécédents de la perception de soutien organisationnel. Parmi celles-ci, l'étude de Wayne et al (2002) révèle que l'information privilégiée provenant des gestionnaires augmente la perception positive de soutien organisationnel des employés.…”
Section: Pratiques De Gestion Des Ressources Humaines Et Perception Dunclassified